Evidence of reducing ethanol content in beverages to reduce harmful use of alcohol. (September 2016) - Rehm, Jürgen; Lachenmeier, Dirk W; Llopis, Eva Jané; Imtiaz, Sameer; Anderson, Peter
Summary: Alcohol use is a major contributor to the burden of gastrointestinal disease. WHO's global strategy to reduce harmful use of alcohol encourages the alcohol industry to contribute to this effort. However, evidence that alcohol producers have contributed to the reduction of harmful use of alcohol is scarce. Reduction of alcoholic strength of beer has been proposed and initiated as one potential way forward. We examine the evidence base for the success of such an initiative. Direct evidence from natural experiments or other controlled studies is scarce. We identified three potential mechanisms for how reduction of alcoholic strength could affect harmful use of alcohol: by current drinkers replacing standard alcoholic beverages with similar beverages of lower alcoholic strength, without increasing the quantity of liquid consumed; by current drinkers switching to no alcohol alternatives for part of the time, thereby reducing their average amount of ethanol consumed; and by initiating alcohol use in current abstainers. The first mechanism seems to be the most promising to potentially reduce harm, but much will depend on actual implementation, and only an independent assessment will be able to identify effects on harmful drinking. The potential of alcoholic strength reduction is independent of initiation by law or by self-initiative of the industry.